Asertive Training As A Control Efforts Angry Emotions In Teenagers - Dinarwiyata Dinarwiyata; Dyah Wijayanti; Nikmatul Fadilah (Humanistic Network for Science and Technology (HNST), 2018)
One of types of normal human emotion is being angry. Unadaptive anger is passive and aggressive, meanwhile, adaptive anger is assertive. Adolescent phase is critical phase in searching for self identity. Uncontrol anger in adolescent phase causes violent behavior and it has negative impact for the personnel, group, and environment. Moreover, this research aimed at identifying the influence of assertive training against the control of teenager’s anger at Junior High School in Surabaya, East Java-Indonesia. The researchers utilized queasy experiment method through pretest – posttest approach with control group by utilizing consecutive sampling technique. Meanwhile, data collection utilized questionnaire. There were two kinds of questionnaires which were used, which were for screening and for prepost-test. Assertive training aimed at improving teenager’s control while they were angry. Research result showed that the decrease of anger was significant between before and after being given assertive training (p < 0.05). The difference of anger score between in control group and in treatment group was significant (p = 0.05). However, assertive training could be used as alternative way in order to improve teenager’s control while they were in angry emotion rather than other therapies. Keywords: Aseertive training, Teeneger, Anger